p45NF-E2 represses Gcm1 in trophoblast cells to regulate syncytium formation, placental vascularization and embryonic growth - Kashif, Muhammed; Hellwig, Andrea; Kolleker, Alexander; Shahzad Hussain, Khurrum; Wang, Hongjie; Lang, Siegfried; Wolter, Juliane; Madhusudhan, Thati; Vinnikov, Ilya A.; Bierhaus, Angelika; Nawroth, Peter Paul; Isermann, Berend (Development, 2011)
Absence of the leucine zipper transcription factor p45NF-E2 results in thrombocytopenia, impaired placental vascularization and intrauterine growth restriction (IUGR) in mice. The mechanism underlying the p45NF-E2-dependent placental defect and IUGR remains unknown. Here, we show that the placental defect and IUGR of p45NF-E2 (Nfe2) null mouse embryos is unrelated to thrombocytopenia, establishing that embryonic platelets and platelet-released mediators are dispensable for placentation. Rather, p45NF-E2, which was hitherto thought to be specific to hematopoietic cells, is expressed in trophoblast cells, where it is required for normal syncytiotrophoblast formation, placental vascularization and embryonic growth. Expression of p45NF-E2 in labyrinthine trophoblast cells colocalizes with that of Gcm1, a transcription factor crucial for syncytiotrophoblast formation. In the absence of p45NF-E2, the width of syncytiotrophoblast layer 2 and the expression of Gcm1 and Gcm1-dependent genes (Synb and Cebpa) are increased. In vitro, p45NF-E2 deficiency results in spontaneous syncytiotrophoblast formation, which can be reversed by Gcm1 knockdown. Increased Gcm1 expression in the absence of p45NF-E2 is dependent on enhanced protein acetylation, including post-translational modification of Gcm1. Increasing and inhibiting acetylation in the placenta of wild-type control embryos phenocopies and corrects, respectively, the changes observed in p45NF-E2-deficient embryos. These studies identify a novel function of p45NF-E2 during placental development: in trophoblast cells, p45NF-E2 represses Gcm1 and syncytiotrophoblast formation via acetylation.